Population-Based Incidence Rates of Cervical Intraepithelial Neoplasia in the Human Papillomavirus Vaccine Era - Benard, Vicki B. (JAMA Oncol, 2017)
IMPORTANCE: A substantial effect of human papillomavirus (HPV) vaccines on reducing HPV-related cervical disease is essential before modifying clinical practice guidelines in partially vaccinated populations. OBJECTIVE: To determine the population-based cervical intraepithelial neoplasia (CIN) trends when adjusting for changes in cervical screening practices that overlapped with HPV vaccination implementation. DESIGN, SETTING, AND PARTICIPANTS: The New Mexico HPV Pap Registry, which captures population-based estimates of both cervical screening prevalence and CIN, was used to compute CIN trends from January 1, 2007, to December 31, 2014. Under New Mexico Administrative Code, the New Mexico HPV Pap Registry, a statewide public health surveillance program, receives mandatory reporting of all cervical screening (cytologic and HPV testing) and any cervical, vulvar, and vaginal histopathological findings for all women residing in New Mexico irrespective of outcome. MAIN OUTCOME MEASURES: Prespecified outcome measures included low-grade CIN (grade 1 [CIN1]) and high-grade CIN (grade 2 [CIN2] and grade 3 [CIN3]). RESULTS: From 2007 to 2014, a total of 13 520 CIN1, 4296 CIN2, and 2823 CIN3 lesions were diagnosed among female individuals 15 to 29 years old. After adjustment for changes in cervical screening across the period, reductions in the CIN incidence per 100 000 women screened were significant for all grades of CIN among female individuals 15 to 19 years old, dropping from 3468.3 to 1590.6 for CIN1 (annual percentage change [APC], −9.0; 95% CI, −12.0 to −5.8; P < .001), from 896.4 to 414.9 for CIN2 (APC, −10.5; 95% CI, −18.8 to −1.2; P = .03), and from 240.2 to 0 for CIN3 (APC, −41.3; 95% CI, −65.7 to 0.3; P = .05). Reductions in the CIN2 incidence were also significant for women 20 to 24 years old, dropping from 1027.7 to 627.1 (APC, −6.3; 95% CI, −10.9 to −1.4; P = .02). CONCLUSIONS AND RELEVANCE: Population-level decreases in CIN among cohorts partially vaccinated for HPV may be considered when clinical practice guidelines for cervical cancer screening are reassessed. Evidence is rapidly growing to suggest that further increases in raising the age to start screening are imminent, one step toward integrating screening and vaccination.